2017
DOI: 10.1177/0001839217700352
|View full text |Cite
|
Sign up to set email alerts
|

The Paradox of Breadth: The Tension between Experience and Legitimacy in the Transition to Entrepreneurship

Abstract: We focus on the paradox generated when prospective entrepreneurs accumulate broad functional experience. On one hand, broad functional experience may facilitate an individual's pursuit of new ventures, as breadth enables the mastery of different skills and access to heterogeneous information and resources. On the other hand, such broad experience might hinder transition into entrepreneurship by imposing the threat of devaluation by key resource providers and thus undermining the legitimacy of entrepreneurial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 100 publications
2
64
1
Order By: Relevance
“…The implications of our results for individuals specializing in tools or topics that have broad applications (e.g., general purpose technologies) remain unclear. Creative workers might also become specialists along one dimension and generalists along another one (Kacperczyk and Younkin, 2017). Besides, individuals might shift strategy over the span of their career (Mannucci and Yong, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The implications of our results for individuals specializing in tools or topics that have broad applications (e.g., general purpose technologies) remain unclear. Creative workers might also become specialists along one dimension and generalists along another one (Kacperczyk and Younkin, 2017). Besides, individuals might shift strategy over the span of their career (Mannucci and Yong, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Audia et al . () use paradox to prime the reader's notion of potential downsides of organizational success; Kacperczyk and Younkin () and Garud et al . () raise the term to offer conceptual reference for their research on legitimacy; Delacour and Leca (), Miron‐Spektor et al .…”
Section: Results: Setting Out a Typology Of Contributing Through Paradoxmentioning
confidence: 99%
“…Marking the study with the conceptual denotation of paradox, scholars put forward points of reference for how one is to navigate throughout the publication's discourse -offering some handhold on how to maneuver an obscure and complex reality. For example, Audia et al (2000) use paradox to prime the reader's notion of potential downsides of organizational success; Kacperczyk and Younkin (2017) and Garud et al (2014) raise the term to offer conceptual reference for their research on legitimacy; Delacour and Leca (2017), Miron-Spektor et al (2011), andWadhwa et al (2017) delineate paradox as a way to grasp the ambiguity present in innovation and disruption. With references to paradox being but sparsely present in the overall textual discourse of these studies, publications in this category were found to use paradox allusion much like a rhetorical trope, guiding the reader's basic apprehension of the contribution as put forward by means of semantic priming.…”
Section: Approach 3: Using Paradox To Verbalize Something Puzzlingmentioning
confidence: 99%
“…We offer evidence that, in industries where quality is difficult to assess (e.g., markets with credence goods), licensure might foster rather than hinder entrepreneurial entry, especially when other quality signals are missing. Because entrepreneurship is associated with high uncertainty, whereby entrepreneurs face the challenge of convincing relevant audiences, such as investors, consumers, or future employees about the validity of their claims (Belenzon, Chatterji, and Daley 2017;Kacperczyk and Younkin 2017), the signaling aspects of licensure might be valuable. More generally, our research highlights the potential benefits of labor-market regulation for entrepreneurial activity when the benefits of signaling outweigh the costs of regulatory compliance-as might be the case in instances when substitute quality signals are missing.…”
Section: Discussionmentioning
confidence: 99%